CREATIVE STEPS IN IMPROVING THE READING ABILITY OF HIGH CLASS STUDENTS THROUGH INTRODUCTION TO NATURE PIR BATEE PUTEH V STATE ELEMENTARY SCHOOL ARONGAN LAMBALEK WEST ACEH - Yulia Riechie; Siti Mayang Sari; Fitriani Manurung; Sariakin; Rita Novita (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The learning process does not rule out the possibility that elementary school students experience reading difficulties. High grade elementary school students' reading difficulties are also found in several elementary schools in various regions, of course this greatly influences the students' learning process in responding to and understanding the lessons given by the teacher. Improving reading skills in high class students at PIR Batee Puteh V State Elementary School, Arongan Lambalek, West Aceh requires a creative and contextual approach. This research explores innovative steps involving the introduction of nature as a means of increasing student literacy, namely: (1) Observation and introduction to the natural surroundings, (2) Selection of reading materials inspired by nature, (3) Integrated science exploration and learning activities, (4) Writing activities based on natural observations, (5) Discussion and reflection together. The author's aim is that through natural exploration activities based on the school environment, students can enrich their reading experience, increase their interest in learning, and provide a deeper understanding of concepts.